POTENTIAL ANTIMICROBIAL IN WHEY AND LACTIC ACID BACTERIA IN SUMBA MARE'S MILK - Sanam, Maxs U. E. (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2022)
Sumba mare’s milk is rich in whey protein, fat, and lactic acid bacteria known to boost antimicrobial activities required in the prevention of diarrhea and inflammation. This study is, therefore, aimed at determining the antibacterial properties of whey and lactic acid bacteria as therapeutic compounds against pathogenic Staphylococcus aureus, SalmonellaTyphimurium, and Salmonella Enteritidis, respectively. The investigations were conducted at the Veterinary Public Health Laboratory of the Faculty of Veterinary Medicine, Nusa Cendana University. Whey antimicrobial test was performed using Salmonella Typhimurium ATCC® 19585 ™ and Staphylococcus aureus, while for lactic acid bacteria, SalmonellaEnteritidis ATCC® 13076 ™ obtained from the Veterinary Public Health Section, Faculty of Veterinary Medicine, Bogor Agricultural University, was applied. However, mare colostrum was acquired from East Sumba, East Indonesia. The results showed the average penicillin inhibitory zones of whey protein were estimated at 20 mm and 17 mm against Staphylococcus aureus. This also revealed the average diameter of the penicillin inhibitory zone and whey protein were equally evaluated at 2.1 mm, although the latter demonstrated sufficient antimicrobial activity against SalmonellaTyphimurium. Furthermore, the lactic acid bacteria inhibitory zone in filtrate and non-filtrates are strongly characterized using the agar method against Salmonella Enteritidis. In conclusion, whey protein and lactic acid bacteria from Sumba mare’s milk have significant antimicrobial potentials during the treatment of Salmonellosis and Staphylococcus aureusinfections.